A method for preparing superabsorbent gastric retention hydrogel for obesity intervention

The double crosslinking hydrogel prepared by step crosslinking method solves the problems of the complex preparation process of existing hydrogels in obesity intervention and the difficult crosslinking direction to control, achieving high superabsorbent and stable retention effects in gastric, with safety and therapeutic effects.

CN119732901APending Publication Date: 2025-04-01HARVEST PHARMA HUNAN CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510027078.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In obesity intervention, existing hydrogels have problems such as complex preparation process, difficult to control crosslinking direction, and easy to scale, resulting in insufficient water absorption and stability in the stomach.

Method used

Using sodium carboxymethylcellulose, glucomannan and citric acid as raw materials, crosslinked sodium carboxymethylcellulose and crosslinked glucomannan were prepared by step crosslinking method, and a hydrogel with a double crosslinked three-dimensional network structure was formed under the action of citric acid.

Benefits of technology

The prepared hydrogel has high super-absorbent properties, with a swelling degree of more than 100 times its own mass, and remains stable in the stomach for 3 to 5 hours, and is biodegradable, ensuring its safety and therapeutic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119732901A_ABST
    Figure CN119732901A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a super absorbent gastric retention hydrogel for obesity intervention, comprising the following steps: S1, preparing cross-linked sodium carboxymethyl cellulose; S2, preparing cross-linked glucomannan; S3, preparing a hydrogel. The preparation method uses sodium carboxymethyl cellulose, glucomannan and citric acid as raw materials, firstly cross-links citric acid with sodium carboxymethyl cellulose and glucomannan to obtain cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan, and then cross-links the cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan under the action of citric acid to obtain a hydrogel with a double cross-linked three-dimensional network structure. The preparation process of the invention is simple, the cross-linking direction is controllable, and it is easy to scale up. The swelling degree of the hydrogel prepared by the preparation method of the invention can reach more than 100 times of its own mass, can be stably retained in the stomach for 3 to 5 hours, and can be biodegradable, ensuring the safety of the hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogel technology, and more specifically to a method for preparing a superabsorbent gastric retention hydrogel for obesity intervention. Background Technology

[0002] Hydrogels are three-dimensional networks that swell but do not dissolve in water; they are hydrophilic polymers with physical or chemical cross-linking structures. Due to the large number of hydrophilic groups in their molecular structure, such as hydroxyl, carboxyl, and amino groups, hydrogels possess exceptional water absorption and retention capabilities, capable of absorbing hundreds or even thousands of times their own weight in water while locking the water within the matrix. Hydrogels are similar in properties to the extracellular matrix and possess flexibility very similar to natural tissues, resulting in excellent biocompatibility. They have wide applications in biomedicine and bioengineering, such as tissue engineering materials, regenerative medicine, wound dressings, drug delivery systems, contact lenses, and stretchable flexible electronic elastomers.

[0003] With the improvement of people's living standards, obesity has become a significant public health problem in today's society. Obesity easily leads to various diseases such as cancer, coronary heart disease, diabetes, and fatty liver, seriously threatening human health. At the same time, obesity accelerates aging and affects lifespan. Currently, obesity intervention methods mainly include improving lifestyle habits, drug treatment, and surgical treatment. However, simply improving lifestyle habits has limited effectiveness in treating morbid obesity. While drug treatment has some therapeutic effect, it is often accompanied by side effects such as vomiting, diarrhea, and endocrine disorders. Surgical treatment can effectively reduce weight, but it is highly invasive and has a long recovery period, making it not the first choice for obesity treatment.

[0004] Therefore, due to the excellent biocompatibility and hydrophilicity of hydrogels, the volume of the hydrogel carrier can be rapidly reduced by drying and dehydration, and it can quickly expand upon reabsorption of water. This allows hydrogels to be used in a novel treatment approach for obesity intervention. The principle is to utilize the swollen carrier to occupy a portion of the gastric volume, thereby reducing the patient's food intake. Simultaneously, the carrier can slow down gastric emptying, reducing the patient's appetite and thus achieving weight loss. An ideal obesity intervention carrier needs to possess swelling properties, mechanical stability, and biodegradability to ensure therapeutic efficacy and avoid potential risks (such as intestinal obstruction).

[0005] However, the polymer chains in existing hydrogels are all randomly cross-linked, and the degree of cross-linking is not controlled. Besides affecting adsorption thermodynamics, the degree of cross-linking also affects the diffusion, mechanical, and degradation properties of the hydrogel. Patent application CN201680011075.7 discloses a hydrogel that uses only carboxymethyl cellulose and citric acid for cross-linking, ultimately forming a single polymer network. This leads to a decrease in the mechanical strength and water absorption of both the polymer and the hydrogel. Patent application CN202311587284.4 discloses a meal replacement gel that uses a one-pot method with konjac glucomannan, pullulan, sodium carboxymethyl cellulose, and citric acid for high-temperature cross-linking in an aqueous solution. However, the one-pot cross-linking product is complex, the cross-linking direction cannot be effectively controlled, and water inhibits the cross-linking reaction, resulting in a low degree of cross-linking and reduced water absorption of the product. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a superabsorbent gastric retention hydrogel for obesity intervention that is simple to prepare, has controllable cross-linking direction, and is easy to scale up.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] A method for preparing a superabsorbent gastric retention hydrogel for obesity intervention includes the following steps:

[0009] S1. Preparation of cross-linked sodium carboxymethyl cellulose: Prepare an aqueous solution of sodium carboxymethyl cellulose and citric acid, mix them evenly by stirring, dry to remove water and obtain a sodium carboxymethyl cellulose and citric acid complex, pulverize the sodium carboxymethyl cellulose and citric acid complex to obtain a complex powder, and heat the complex powder at a temperature of at least 100°C to cross-link the sodium carboxymethyl cellulose with citric acid to form cross-linked sodium carboxymethyl cellulose.

[0010] S2. Preparation of cross-linked glucomannan: Prepare an aqueous solution of glucomannan and citric acid, mix them evenly by stirring, dry to remove water and obtain a glucomannan and citric acid complex, pulverize the glucomannan and citric acid complex to obtain a complex powder, and heat the complex powder at a temperature of at least 100°C to cross-link the glucomannan with citric acid to form cross-linked glucomannan.

[0011] S3. Preparation of hydrogel: Prepare an aqueous solution of the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid. After stirring and mixing evenly, dry to remove water and obtain a complex of cross-linked sodium carboxymethyl cellulose, cross-linked glucomannan and citric acid. Crush the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid complex to obtain a complex powder. Heat the complex powder at a temperature of at least 100°C to cross-link the sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid to form a hydrogel; wherein the weight ratio of the cross-linked sodium carboxymethyl cellulose to the cross-linked glucomannan is 1:1.

[0012] As a further improvement to the above technical solution: in the aqueous solution of sodium carboxymethyl cellulose and citric acid in step S1, the amount of citric acid used is at most 0.5% of the amount of sodium carboxymethyl cellulose used. Preferably, the amount of citric acid used is 0.1% of the amount of sodium carboxymethyl cellulose used.

[0013] As a further improvement to the above technical solution: in the aqueous solution of glucomannan and citric acid in step S2, the amount of citric acid is at most 0.5% of the amount of glucomannan. Preferably, the amount of citric acid is 0.05% of the amount of glucomannan.

[0014] As a further improvement to the above technical solution: in step S3, when preparing the aqueous solution of the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid, the amount of water used is at least 20 times the total amount of the cross-linked sodium carboxymethyl cellulose and the cross-linked glucomannan.

[0015] As a further improvement to the above technical solution: when heating the powder of the cross-linked sodium carboxymethyl cellulose and the cross-linked glucomannan and citric acid complex in step S3, the heating temperature is 130±2℃ and the heating time is 2 hours.

[0016] A hydrogel manufactured by the method described above.

[0017] A pharmaceutical composition comprising the above-described hydrogel and a pharmaceutically acceptable carrier or excipient.

[0018] As a further improvement to the above technical solution: the pharmaceutical composition is in a form suitable for oral administration, preferably in the form of capsules.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] This invention discloses a method for preparing a superabsorbent gastric retention hydrogel for obesity intervention. Using sodium carboxymethyl cellulose, glucomannan, and citric acid as raw materials, citric acid is first cross-linked with sodium carboxymethyl cellulose and glucomannan to obtain cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan. Then, under the action of citric acid, the cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan are further cross-linked to obtain a double-crosslinked three-dimensional network structure hydrogel. The preparation process of this invention is simple, the cross-linking direction is controllable, and it is easily scalable. The hydrogel prepared using this method can swell to more than 100 times its own weight, can stably remain in the stomach for 3 to 5 hours, and is biodegradable, ensuring the safety of the hydrogel. It can be encapsulated in standard commercially available edible capsules for oral administration, rapidly swelling in gastric juice to provide a lasting feeling of fullness, helping to reduce patients' appetite and energy intake, thus playing a role in obesity intervention. Attached Figure Description

[0021] Figure 1 This invention discloses the synthesis mechanism of the hydrogel in the preparation method of the superabsorbent gastric retention hydrogel for obesity intervention.

[0022] Figure 2 This is a structural diagram of the hydrogel prepared by the method for preparing the superabsorbent gastric retention hydrogel for obesity intervention according to the present invention.

[0023] Figure 3 This is a graph showing the swelling degree of the hydrogel in SGF / water (1:8) and SIF at different time points in this invention.

[0024] Figure 4 This is a graph showing the elastic modulus curves of the hydrogel in SGF / water (1:8) and SIF at different time points in this invention. Detailed Implementation

[0025] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments, but this does not limit the scope of protection of the present invention. The materials and instruments used in the following embodiments are all commercially available products.

[0026] The present invention relates to a method for preparing a superabsorbent gastric retention hydrogel for obesity intervention, comprising the following steps:

[0027] S1. Preparation of cross-linked sodium carboxymethyl cellulose;

[0028] Step S1 includes:

[0029] S1.1 Prepare an aqueous solution of sodium carboxymethyl cellulose and citric acid; wherein the amount of citric acid used is at most 0.5% of the amount of sodium carboxymethyl cellulose used; preferably, the amount of citric acid used is 0.1% of the amount of sodium carboxymethyl cellulose used;

[0030] S1.2. Stir and mix the above aqueous solution of sodium carboxymethyl cellulose and citric acid until homogeneous;

[0031] S1.3. Dry the aqueous solution of sodium carboxymethyl cellulose and citric acid to form a sodium carboxymethyl cellulose and citric acid complex;

[0032] S1.4. Crush the above sodium carboxymethyl cellulose and citric acid complex to obtain a complex powder;

[0033] S1.5 The compound powder of sodium carboxymethyl cellulose and citric acid is heated and dried at a temperature of at least 100°C, thereby causing sodium carboxymethyl cellulose to crosslink with citric acid and form crosslinked sodium carboxymethyl cellulose.

[0034] S2: Preparation of cross-linked glucomannan;

[0035] Step S2 includes:

[0036] S2.1. Prepare an aqueous solution of glucomannan and citric acid; wherein the amount of citric acid is at most 0.5% of the amount of glucomannan; preferably, the amount of citric acid is 0.05% of the amount of glucomannan.

[0037] S2.2. Stir and mix the above aqueous solution of glucomannan and citric acid until homogeneous;

[0038] S2.3. Dry the aqueous solution of glucomannan and citric acid to form a glucomannan and citric acid complex;

[0039] S2.4. Crush the above glucomannan and citric acid complex to obtain a complex powder;

[0040] S2.5. The above-mentioned glucomannan and citric acid complex powder is heated and dried at a temperature of at least 100°C, thereby causing the glucomannan and citric acid to crosslink and form crosslinked glucomannan.

[0041] S3. Preparation of hydrogel;

[0042] Step S3 includes:

[0043] S3.1 Prepare an aqueous solution of croscarmellose sodium, croscarmellose glucomannan and citric acid and mix them evenly; wherein the weight ratio of croscarmellose sodium to croscarmellose glucomannan is 1:1, and the amount of water used is at least 20 times (by mass) the total amount of croscarmellose sodium and croscarmellose glucomannan.

[0044] S3.2, Drying the aqueous solution of step S3.1 to form a complex of cross-linked sodium carboxymethyl cellulose, cross-linked glucomannan and citric acid;

[0045] S3.3, Crush the complex from step S3.2 to produce complex powder;

[0046] S3.4. The composite powder from step 3.3 is heated and dried at a temperature of at least 100°C, thereby crosslinking sodium carboxymethyl cellulose, crosslinked glucomannan and citric acid to form the hydrogel.

[0047] This invention uses sodium carboxymethyl cellulose, glucomannan, and citric acid as raw materials. First, citric acid is cross-linked with sodium carboxymethyl cellulose and glucomannan respectively to obtain cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan. Then, under the action of the cross-linking agent citric acid, the cross-linked sodium carboxymethyl cellulose and cross-linked glucomannan are cross-linked again to obtain a double-crosslinked three-dimensional network hydrogel. The preparation process of this invention is simple, and compared with the one-pot method, the cross-linking direction is controllable and easy to scale up. The hydrogel prepared by the method of this invention can swell to more than 100 times its own weight, can remain stably in the stomach for 3 to 5 hours, and is biodegradable, ensuring the safety of the hydrogel. It can be encapsulated in standard commercially available edible capsules for oral administration. It rapidly swells in gastric juice to provide a long-lasting feeling of fullness, helping to reduce patients' appetite and energy intake, thus playing a role in obesity intervention.

[0048] The present invention will be further illustrated by the following examples.

[0049] Example 1: Preparation of cross-linked carboxymethyl cellulose

[0050] Add 85.0 kg of purified water and 5.0 g of citric acid monohydrate to a 100 L homogenizer. Stir for 5 minutes, then add 5.0 kg of sodium carboxymethyl cellulose and mix for 12 hours. Transfer the material from the homogenizer to an enamel drying tray using a spoon. Spread the material evenly using a plastic scraper. Control the temperature at 50–75 °C and dry with forced air until the loss on drying is ≤10.0%. Discharge the material. Grind the material using a universal grinder. Spread the ground material evenly on the enamel drying tray, controlling the material thickness to ≤0.5 cm. Dry at 120 ± 2 °C for 1 hour, then discharge the material.

[0051] Example 2: Preparation of cross-linked glucomannan

[0052] Add 80.0 kg of purified water and 2.5 g of citric acid monohydrate to a 100 L homogenizer. Stir for 5 minutes, then add 5.0 kg of glucomannan and mix for 10 hours. Transfer the material from the homogenizer to an enamel drying tray using a spoon. Spread the material evenly using a plastic scraper. Control the temperature at 60–85 °C and dry with forced air until the loss on drying is ≤10.0%. Discharge the material. Grind the material using a universal grinder. Spread the ground material evenly on the enamel drying tray, controlling the material thickness to ≤0.5 cm. Dry at 110 ± 2 °C for 1 hour, then discharge the material.

[0053] Example 3: Hydrogel Preparation

[0054] Add 160.0 kg of purified water and 2.5 g of citric acid monohydrate to a 200 L homogenizer. After stirring for 5 minutes, add 4.0 kg of croscarmellose sodium and 4.0 kg of croscarmellose glucomannan, and mix for 12 hours. Transfer the material from the homogenizer to an enamel drying tray using a spoon, spread it evenly with a plastic scraper, and dry it at a controlled temperature of 50–75 °C until the loss on drying is ≤10.0%. Discharge the material. Grind the material using a universal grinder. Spread the ground material evenly on the enamel drying tray, controlling the material thickness to ≤0.5 cm, and dry it at 130 ± 2 °C for 2 hours to obtain the hydrogel.

[0055] Example 4: Characterization of hydrogels

[0056] 1. Preparation of simulated gastric juice (SGF) / water (1:8):

[0057] The reagents used to prepare the SGF / water (1:8) solution were purified water, sodium oxide, 1M hydrochloric acid, and pepsin.

[0058] Pour approximately 880 ml of water into a 1 L graduated cylinder. Place the graduated cylinder on a magnetic stirrer, add the magnetic rod, and begin stirring. Begin monitoring the pH of the water using a pH meter. Add sufficient 1 M hydrochloric acid to adjust the pH to 2.1 ± 0.1. Add 0.2 g NaCl and 0.32 g pepsin. Continue stirring the solution until completely dissolved. Remove the magnetic rod and pH electrode from the graduated cylinder.

[0059] 2. Preparation of simulated intestinal fluid:

[0060] The simulated intestinal fluid (SIF) test solution, formally named "Simulated Intestinal Fluid (Test Solution)," was prepared according to the USP method. Potassium dihydrogen phosphate (6.8 g) was dissolved in 250 mL of water, and then 77 mL of 0.2 N sodium hydroxide and 500 mL of water were added. Then, 10.0 g of trypsin was added, and the resulting solution was adjusted to pH 6.8 ± 0.1 with 0.2 N sodium hydroxide or 0.2 N hydrochloric acid, and finally diluted with water to a volume of 1000 mL.

[0061] 3. Determination of the medium absorption ratio (swelling degree) in SGF / water (1:8):

[0062] The media absorption ratio (swelling degree) of the hydrogel in SGF / water (1:8) and simulated intestinal fluid (SIF) was determined according to the following scheme.

[0063] Place a suitable dry glass funnel on a stand and pour 40.0 ± 1.0 g of purified water into the funnel. Let it stand until no water droplets are visible at the neck of the funnel (approximately 5 minutes), then wipe the top of the funnel dry with absorbent paper. Place the funnel into an empty and dry glass beaker (beaker #1), place them on a balanced scale, and record the weight of the empty apparatus (W). 空 Place the magnetic stir bar in a 100 mL beaker (beaker #2), and balance beaker #2 on a balance. Add 40.0 ± 1.0 g of the SGF / water (1:8) solution prepared as described above to beaker #2. Place beaker #2 on a magnetic stirrer and stir gently at room temperature. Accurately weigh 0.250 ± 0.005 g of hydrogel powder (W) using weighing paper. 干 Add the powder to beaker #2 and gently stir with a magnetic stirrer for 30 ± 2 minutes without creating a vortex. Remove the stir bar from the resulting suspension, place the funnel on a stand and pour the suspension into the funnel. Collect any remaining material with a spatula and drain the material for 10 ± 1 minutes. Place the drained material into beaker #1 and weigh it (W). 毛 The dielectric absorbance ratio (MUR) is calculated as follows:

[0064] MUR=(W 溶 -W 干 ) / W 干

[0065] W 溶 This is the weight of the swollen hydrogel, calculated as follows:

[0066] W 溶 =W 毛 –W 空

[0067] W 干 This is the weight of the initially dried sample.

[0068] For each hydrogel sample, the MUR was measured in triplicate, and the reported MUR was the average of the three measurements.

[0069] 4. Determination of elastic modulus:

[0070] After the MUR of each sample was measured, a rheometer (model: MARS40 rotational rheometer, manufacturer: Shanghai Hengze Technology Co., Ltd.) was used to perform a scanning frequency test on the material and determine the value at an angular frequency of 10 rad / s. This measurement was performed in triplicate. The reported elastic modulus value is the average of the three measurements.

[0071] The hydrogel obtained in Example 3 was immersed in simulated gastric fluid (SGF) / water (1:8) and simulated intestinal fluid (SIF) and allowed to swell at 37°C until equilibrium was reached. The degree of swelling and elastic modulus of each fluid were determined at different time points. The results are shown in Table 1, and the swelling curves at different time points are attached. Figure 3 As shown in the attached figure, the elastic modulus curves at different time points are as follows. Figure 4 As shown, the results indicate that the hydrogel can swell to at least 100 times its own mass in simulated gastric and intestinal fluids. The hydrogel can remain stably in the stomach for 3 to 5 hours and maintain structural stability under simulated gastric and intestinal fluid conditions, thereby providing a lasting feeling of fullness, helping to reduce patients' appetite and energy intake, and playing a role in obesity intervention.

[0072] Table 1: Swelling degree and elastic modulus of hydrogels in SGF / water (1:8) and SIF at different time points under the condition of 37℃.

[0073] Swelling time (min) MUR (swelling degree) SGF / water (1:8) MUR (swelling degree) SIF Elastic modulus (Pa) SGF / water (1:8) Elastic modulus (Pa) SIF (intestinal fluid) 60 163.1 120.1 4421 3540 120 160.5 115.5 3300 2845 180 155.6 109.6 3014 2250 240 148.7 103.7 2562 1648 300 140.3 100.3 1857 940

[0074] 5. Effect of different cross-linking temperatures on the swelling degree of hydrogels

[0075] 100g of the material prepared according to Example 3 was pulverized using a universal pulverizer. The pulverized material was divided into 5 equal portions and spread evenly on enamel drying trays. These trays were then placed in drying ovens at 100±2℃, 110±2℃, 120±2℃, 130±2℃, and 140±2℃ respectively, and dried for 2 hours. The swelling degree was then measured at 37℃ after 60 minutes of swelling in simulated gastric juice (SGF) / water (1:8). The results are shown in Table 2. Within the drying temperature range of 100–130℃, the swelling degree increased continuously with increasing drying temperature. However, when the drying temperature reached 140±2℃, the swelling degree decreased rapidly. Therefore, the hydrogel exhibits better swelling performance at a drying temperature of 130±2℃.

[0076] Table 2: Swelling degree of hydrogels at drying temperatures of 100±2℃, 110±2℃, 120±2℃, 130±2℃, and 140±2℃ in SGF / water (1:8) at 37℃.

[0077] Drying temperature (°C) MUR (swelling degree) SGF / water (1:8) 100 60.3 110 95.6 120 126.5 130 162.9 140 83.4

[0078] 6. Effect of different cross-linking times on the swelling degree of hydrogels

[0079] 100g of the material prepared according to Example 3 was pulverized using a universal pulverizer. The pulverized material was spread evenly on an enamel drying tray and dried at 130±2℃ for 1, 2, 3, 4, and 5 hours. Samples of 10g were taken at 37℃ and their swelling degree was measured after 60 minutes of swelling in simulated gastric juice (SGF) / water (1:8). The results are shown in Table 3. As the drying time increased, the degree of cross-linking of the hydrogel gradually increased, while its swelling degree showed a trend of first increasing and then decreasing. In particular, when the drying time was controlled between 1 and 2 hours, the degree of cross-linking of the hydrogel could be precisely controlled, thereby ensuring its excellent swelling performance. This time period is crucial for maintaining the ideal degree of cross-linking and swelling performance of the hydrogel.

[0080] Table 3: Swelling of hydrogels at 37℃ in SGF / water (1:8) after drying at 130±2℃ for 1, 2, 3, 4, and 5 hours.

[0081] Drying time (hours) MUR (swelling degree) SGF / water (1:8) 1 153.1 2 161.4 3 140.5 4 100.3 5 64.7

[0082] Comparative Example 1:

[0083] Referring to the patent application number CN202311587284.4, 90.0 g of hydrogel was prepared, and its swelling in simulated gastric juice (SGF) / water (1:8) and water was measured at 37°C. The results are shown in Table 4. The results show that Example 3, prepared by the stepwise crosslinking method, exhibits significantly better swelling performance than Comparative Example 1, prepared by the one-pot method.

[0084] Table 4: Swelling of hydrogels in SGF / water (1:8) and water at 37°C

[0085] materials MUR (swelling degree) SGF / water (1:8) MUR (swelling degree) water Comparative Example 1 22.1 32.2 Example 3 163.1 170.2

[0086] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention, or modify them into equivalent embodiments, without departing from the scope of the present invention. Therefore, any simple modifications, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention, without departing from the scope of the present invention, should fall within the protection scope of the present invention.

Claims

1. A method for preparing a superabsorbent gastric retention hydrogel for obesity intervention, characterized in that: The following steps are involved: S1. preparing cross-linked sodium carboxymethyl cellulose: preparing an aqueous solution of sodium carboxymethyl cellulose and citric acid, stirring and mixing them uniformly, drying to remove water and obtain a complex of sodium carboxymethyl cellulose and citric acid, crushing the complex of sodium carboxymethyl cellulose and citric acid to obtain a complex powder, and heating the complex powder at a temperature of at least 100° C. to cross-link the sodium carboxymethyl cellulose and citric acid to form cross-linked sodium carboxymethyl cellulose; S2, preparing cross-linked glucomannan: preparing an aqueous solution of glucomannan and citric acid, stirring and mixing them uniformly, drying to remove water and obtain a glucomannan and citric acid complex, crushing the glucomannan and citric acid complex to obtain a complex powder, and heating the complex powder at a temperature of at least 100° C. to cross-link the glucomannan and citric acid to form a cross-linked glucomannan; S3. Preparing a hydrogel: preparing an aqueous solution of the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid, stirring and mixing them uniformly, drying to remove water and obtaining a complex of the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid, crushing the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid complex to obtain a complex powder, and heating the complex powder at a temperature of at least 100° C. to cross-link the sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid to form a hydrogel; wherein the weight ratio of the cross-linked sodium carboxymethyl cellulose to the cross-linked glucomannan is 1:

1.

2. The method for preparing the super absorbent gastric retention hydrogel for obesity intervention according to claim 1, characterized in that: In the aqueous solution of sodium carboxymethyl cellulose and citric acid in step S1, the amount of citric acid used is at most 0.5% of the amount of sodium carboxymethyl cellulose used.

3. The method for preparing the super absorbent gastric retention hydrogel for obesity intervention according to claim 2, characterized in that: In the aqueous solution of sodium carboxymethyl cellulose and citric acid in step S1, the amount of citric acid used accounts for 0.1% of the amount of sodium carboxymethyl cellulose used.

4. The method for preparing the super absorbent gastric retention hydrogel for obesity intervention according to claim 1, characterized in that: In the aqueous solution of glucomannan and citric acid in step S2, the amount of citric acid used is at most 0.5% of the amount of glucomannan used.

5. The method for preparing the superabsorbent gastric retention hydrogel for obesity intervention according to claim 4, characterized in that: In the aqueous solution of glucomannan and citric acid in step S2, the amount of citric acid used accounts for 0.05% of the amount of glucomannan used.

6. The method for preparing the super absorbent gastric retention hydrogel for obesity intervention according to claim 1, characterized in that: In step S3, when preparing the aqueous solution of the cross-linked sodium carboxymethyl cellulose, the cross-linked glucomannan and citric acid, the amount of water used is 20 times the total amount of the cross-linked sodium carboxymethyl cellulose and the cross-linked glucomannan.

7. The method for preparing the super absorbent gastric retention hydrogel for obesity intervention according to claim 6, characterized in that: In step S3, when heating the powders of the cross-linked sodium carboxymethyl cellulose and the cross-linked glucomannan and citric acid complex, the heating temperature is 130±2° C. and the heating time is 2 hours.

8. A hydrogel produced by the method of any one of claims 1 to 7.

9. A pharmaceutical composition comprising the hydrogel according to claim 8, and a pharmaceutically acceptable carrier or excipient.

10. The pharmaceutical composition of claim 9, which is in a form suitable for oral administration.

Citation Information

Patent Citations

  • Method for producing hydrogels coupling high elastic modulus and absorbance

    CN107250164A

  • Meal replacement gel as well as preparation method and application thereof

    CN117598493A